Infrared emissivity of Sr doped lanthanum manganites in coating form - "Shen Xingmei, E-mail: xxxxmx@126.com [Anhui Provincial Key Laboratory of Metallurgy Engineering and Resources Recycling, Anhui University of Technology, Ma'anshan, Anhui Province 243002 (China)]"; "Liaosha, Li"; "Xingrong, Wu"; "Zhifang, Gao [Anhui Provincial Key Laboratory of Metallurgy Engineering and Resources Recycling, Anhui University of Technology, Ma'anshan, Anhui Province 243002 (China)]"; "Guoyue, Xu [College of Material Science and Engineering, Nanjing University of Aeronautics and Astronautics, Yu Dao Street 29, Nanjing 210016 (China)]" (2011)
Highlights: > LSMO and epoxy modified polyurethane as pigment and resin matrix, respectively. > The {epsilon}{sub N} of the coating decreases with the increase of LSMO. > Surface roughness has no significant effect on the emissivity of the coating. > Variable-emissivity property of the coating remains unchanged before and after ultraviolet irradiation. - Abstract: The Sr doped lanthanum manganite coatings were prepared using Lasub 0.8Srsub 0.2MnOsub 3 particles and epoxy modified polyurethane as pigment and resin matrix, respectively. The structure, morphology, surface roughness and infrared normal emissivity ({epsilon}{sub N}) in the 3-5 and 8-14 mum wavebands of the samples were systematically investigated. With the increase of Lasub 0.8Srsub 0.2MnOsub 3 pigment, the {epsilon}{sub N} of the coatings decreases and the {epsilon}{sub N} values in the 8-14 mum waveband are higher than those in the 3-5 mum waveband. The surface roughness has no significant effect on the infrared emissivity of LSMO coatings. For 50% LSMO coating, the sample shows variable-emissivity property in the 8-14 mum waveband and the emissivity property remains unchanged before and after ultraviolet irradiation.
Keywords: "36 MATERIALS SCIENCE"; "ABSORPTION"; "CERAMICS"; "DOPED MATERIALS"; "EMISSIVITY"; "EPOXIDES"; "IRRADIATION"; "LANTHANUM"; "MORPHOLOGY"; "PARTICLES"; "PIGMENTS"; "POLYURETHANES"; "REFLECTION"; "RESINS"; "ROUGHNESS"; "SOLIDS"; "SURFACES"; "VISIBLE RADIATION"; "ELECTROMAGNETIC RADIATION"; "ELEMENTS"; "MATERIALS"; "METALS"; "OPTICAL PROPERTIES"; "ORGANIC COMPOUNDS"; "ORGANIC OXYGEN COMPOUNDS"; "ORGANIC POLYMERS"; "PETROCHEMICALS"; "PETROLEUM PRODUCTS"; "PHYSICAL PROPERTIES"; "PLASTICS"; "POLYAMIDES"; "POLYMERS"; "RADIATIONS"; "RARE EARTHS"; "SORPTION"; "SURFACE PROPERTIES"; "SYNTHETIC MATERIALS"